Understanding the values of Islamic economics and Javanese philosophy pertaining to the work ethic of Muslim merchants in Salatiga - Agus Waluyo (IAIN Salatiga, 2022)
The work ethic of Javanese Muslim merchants may originate from religious teachings and Javanese philosophical values. Islamic teachings and Javanese philosophy contain values that edify prudence, caution, precision, optimism, patience, trust in God, harmony, cooperation, and mutual help, which result in a particular work ethic. Muslim merchants in traditional markets, still maintain work ethic manifested by economic practices based on Javanese philosophical aphorisms and Islamic teachings. This study is aimed at analyzing Muslim merchants’ understanding of work ethic as a motive for their actions in manifesting Islamic teachings and Javanese philosophical values aligned with the purposes of sharia (maqasid sharia). Case samples for the study were collected in Salatiga’s traditional markets. The study used the qualitative approach. Max Weber’s social action theory and Abdul Madjid Najjar’s maqasid sharia were used in the analysis. The study results show that merchants’ work ethic begins with their understanding of Islamic economics and Javanese philosophy, which are internalized in their attitude, behavior, and action. The merchants’ behavior, containing substantial values of Islamic teachings and Javanese philosophy, suggests the existence of instrumentally rational, value rational, affectual, and traditional social actions. The merchants’ motivations are categorized as efforts to realize maqasid by maintaining values of human life, human self, society, and physical environment. The merchants’ attitude has fulfilled the indicators for safeguarding faith and rights, human self and intellect, social entity and posterity, and wealth and ecology.